Pola Pikir Perempuan dalam 5 Lagu Campursari Populer Tahun 2019-Awal 2020 Kajian Dekonstruksi - Fadilah, Muhamad Rizkiyono; Werdiningsih, Yuli Kurniati; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2021)
The purpose of this study was to determine the mindset of women in Campursari songs using a deconstruction study. The formulation of the problem in this study is how the mindset of women in Campursari songs using deconstruction studies. This research is included in descriptive qualitative research, because the analysis in this study is a description. The data source used is the text of the Campursari song entitled Balungan Kere, Cidro, Penak Kanca, Kartonyono Medot Janji, and Pamer Bojo. The method used in this research is writing, recording, grouping the data, then the data that has been collected is analyzed using data reduction techniques, data interpretation, and data verification. The result of this research is that there is a deconstruction of the opinion / discourse about Javanese women in Serat Wulang Putri above, it can be concluded that Javanese women are very synonymous with Javanese culture such as speaking soft words, being calm, silent (calm), disliking conflict, emphasizing harmony, uphold family values, able to understand and understand others, polite, high self-control, endurance to suffer high, play a role economically and faithfully. Javanese women are women who really uphold Javanese culture. Some other characteristics of Javanese people are patience and neriman (patience and acceptance with grace).